Young offenders and open custody - Pettersson, Tove (Routledge frontiers of criminal justice, 2017)
Introduction -- Total institutions, discipline and power -- Studying open custody, re-offending and institutional everyday life -- Youth and staff narratives about youth custody sentences -- Youth and staff narratives about the time subsequent to youth custody -- Re-offending and custodial openness -- The significance of custodial openness